Hybrid Materials: Theranostic USPIO‐Loaded Microbubbles for Mediating and Monitoring Blood‐Brain Barrier Permeation (Adv. Funct. Mater. 1/2015). (January 2015) - Lammers, Twan; Koczera, Patrick; Fokong, Stanley; Gremse, Felix; Ehling, Josef; Vogt, Michael; Pich, Andrij; Storm, Gert; van Zandvoort, Marc; Kiessling, Fabian
<x xml:space="preserve">Abstract</x> Enabling safe and efficient drug delivery across the blood‐brain barrier (BBB) remains to be challenging. On page 36 of this issue, T. Lammers, P. Koczera, F. Kiessling, and colleagues show that polymer‐based microbubbles, containing iron oxide nanoparticles within their shell, can be employed to mediate and monitor BBB permeation. Such theranostic constructs and concepts are considered to be useful for tailoring the treatment of central nervous system disorders. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>